Knowledge, attitudes, experience and behaviour of frontline health care workers during the early phase of 2009 influenza A(H1N1) pandemic, Birmingham, UK. (January 2015) - Edeghere, Obaghe; Fowler, Tom; Wilson, Fay; Caspa, Richard; Raichand, Smitri; Kara, Edna; Janmohamed Rampling, Sumi; Olowokure, Babatunde
Objectives: During the early ('containment') phase of the influenza A(H1N1) pandemic, when the severity of the pandemic was unclear, health care workers (HCWs) across the UK were deployed to swab and prescribe antiviral drugs to suspected cases. This study describes the knowledge, attitudes, experience and behaviour of frontline HCWs in Birmingham, West Midlands, during this period. Methods: During June 2009, a 25-item semi-structured questionnaire was used to survey HCWs who undertook defined clinical duties as part of the public health response during the early phase of the pandemic. Participants were clinical staff based in a primary care out-of-hours service provider. Results: The response rate was 50% ( n  = 20). All respondents provided direct clinical care that necessitated prolonged close contact with potentially infectious cases. Knowledge and use of personal protective equipment and infection control procedures was consistently high. However, the main source of infection control advice was local guidance. Uptake of, and attitude towards, vaccination as a preventive measure and antiviral prophylaxis was poor. Conclusions: HCWs were prepared to provide an essential health care response during the pandemic even when the severity of disease was unclear. However, more needs to be done to change health care workers' negative attitudes towards taking antivirals and receiving influenza vaccination.